Analisis Persepsi Guru dalam Melaksanakan Pembelajaran Membaca Permulaan di Kelas 1 SD Negeri Sungai Raya - Septiarini, Siti Aisyah; Afrayaningsih, Yunika; Nurhaidah, Nurhaidah (CV. Ulil Albab Corp, 2024)
This study aims to explore and analyze the views and perceptions of teachers related to the reading learning process at the initial level in grade I elementary school. The research method used was a qualitative approach with in-depth interviews with a number of grade I teachers in both elementary schools, namely at SD Negeri 51 Sungai Raya and SD Negeri 01 Sungai Raya. The results showed that teacher perception has a significant role in directing reading learning approaches and strategies. These findings reveal diverse views on the use of methods, teaching materials, and challenges faced in teaching beginning reading. By analyzing the teacher's perspective, this study provides insight into the factors that influence the effectiveness of reading learning in the early stages of Education. This research has practical implications for curriculum development and teacher training, with the aim of improving the quality of reading learning in grade I elementary school. The results of this study can be a valuable source of information for education practitioners in supporting the development of reading skills in early childhood. By exploring their perceptions, this thesis provides valuable insights for the development of more effective learning methods. The results of this study are expected to provide guidance to education practitioners in improving the quality of reading learning at the beginning level, so that the contribution to children's literacy skills can be more optimal.